Alphachloralose intoxication: A retrospective study on epidemiology, clinical presentation, and management in an adult emergency department in Morocco - El Mehdi Samali; Abdelghafour El Koundi; Amine Meskine; Hicham Balkhi; Mohammed Moussaoui (African Journal of Emergency Medicine, 2025)
Background: Alphachloralose, initially used as a hypnotic and anesthetic, is now restricted to rodenticides. Despite limited medical use, it remains accessible in North Africa, contributing to intentional poisonings. Poisoning primarily presents with neurological and respiratory symptoms, posing a significant public health concern. This study describes the epidemiological, clinical, and therapeutic characteristics of alphachloralose poisoning cases admitted to the adult emergency department of a university hospital in Casablanca, Morocco. Methods: A retrospective study analyzed emergency department records for alphachloralose poisoning cases from October 2022 to June 2023. Poisoning was confirmed based on clinical presentation, witness accounts, and/or biological toxicological evidence. Data on demographics, exposure circumstances, clinical features, interventions, and outcomes were extracted. Severity was evaluated using the Poisoning Severity Score (PSS), grading the severity into five levels from 0 (no symptoms) to 4 (fatal). Hospital stay duration and complications were also assessed. Results: Some 53 cases were included, with mean age of patients 27 years, and a male-to-female ratio of 0.83. Suicidal ingestion accounted for the vast majority of cases (98 %). Alphachloralose was exclusively ingested in powdered form, as no other formulations are available in Morocco. Neurological and respiratory disturbances were the most common clinical manifestations, with 28 % of cases classified as severe according to the PSS. Gastric lavage was performed in 52.8 % of cases, benzodiazepines were administered in 54 %, and 39.6 % of patients required intubation. The median time to admission to intensive care was 5 h. The average duration of hospitalization was 2.4 ± 1.2 days. Although one fatality occurred, 98 % of cases recovered fully without complications, emphasizing the importance of early and appropriate management. Conclusion: Alphachloralose poisoning is a significant toxicological concern in North Africa due to its availability and misuse. Severe symptoms are frequent, but early intervention leads to favorable outcomes. Public health measures focusing on regulation and education are essential.